Enabling factors and constraints for the adoption of animal welfare-enhancing technologies among Finnish dairy farmers - Kallioniemi, Marja K.; Kymäläinen, Hanna-Riitta; Niemi, Jarkko K. (Frontiers in Animal Science, 2024)
The restructuring of dairy farm production has resulted in enlarged unit sizes and production capacities on commercial farms in Finland. Concurrently, the livestock sector is facing high expectations and pressure to enhance farm animal welfare. Many dairy farms have invested in state-of-the-art technology, e.g. the proportion of milk milked by robots had risen 41% by 2019 in Finland. Using a survey framework based on the constructs of the Ttheory of Pplanned Bbehavior (TPB), our aim was to explore which factors may limit farmers' willingness to adopt animal welfare-enhancing solutions. The decision to adopt a technology can be seen as a holistic issue that is affected by farmer attitudes, farm-specific constraints, and information provided by trusted sources. The financial situation of farms, appropriate technological devices, animal welfare, and human well-being should all be considered holistically. We utilize our exploratory survey sample as an indicator for discussing the current situation. The most critical constraints were related to financial issues, farmers' personal coping challenges, and device operation problems in the barn environment. To promote the adoption of new technologies, farmers require technical and other support from trusted groups and evidence on the functionality of the technology. The insights from this exploratory study highlight the importance of available resources; the most important deficiencies related to available resources were financial and personal capacity to cope with duties.